Класична юридична освіта у центрі правової культури суспільства - Дудченко, Валентина Віталіївна; Дудченко, Валентина Витальевна; Dudchenko, Valentina (My University, 2011)
The essence of classics in law is determined together with its specific characteristics in the foreign legal education history and nowadays. Syncretism of roman law and ethics, formular law system, natural and positive law, contractual nature of justice, pretor's right, recodification were analyzed.
Дудченко В. В. Класична юридична освіта у центрі правової культури суспільства / В. В. Дудченко // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 252-260.
Keywords: синкретизм права і етики; формулярна система права; природне й позитивне право; договірна природа справедливості; право претора; рекодифікація; синктретизм права и этики; формулярная система права; природное и позитивное право; договорная природа справедливости; право претора; рекодификация; syncretism of law and ethics; formulary system of law; natural and positive law; contract nature of justice; right praetor; recodification